KaPeu: Political Awareness Strategies for Generation Z through Social Media in the 2024 Elections - Ayu, Alrisa (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
Generation Z and social media are an integral part of the Society 5.0 era. Therefore, in view of the simultaneous elections in 2024, a proper political awareness strategy of KPU Provinsi Jawa Timur for generation Z through social media is necessary. This paper aims to provide political education solutions to Generation Z through social media, particulary in East Java for the 2024 elections with the “Kamu Perlu Tau” (KaPeu) program. The KaPeu contains elections and democracy information presented in a unique, interesting, informative, and according to the tastes of Generation Z. The research method uses a descriptive qualitative approach. Meanwhile, used in-depth interviews and content analysis techniques. In this research, the KaPeu uses more social media, namely Instagram, Facebook, and Twitter, which largely belong to Generation Z. Compared to previous studies, none has discussed the KaPeu as a means of political education. The results of the analysis show that the KaPeu published by the KPU Provinsi Jawa Timur functions to disseminate election and democracy information, build public engagement, increase public awareness, understanding of the importance of elections and democracy, explore aspirations; understanding, contribution to political and electoral information provided by the KPU Provinsi Jawa Timur to improve the quality of community participation, particularly in East Java.